IOT Based Oil Condition Monitoring of Wind Turbine Gearboxes with Smart Sensor Technology - L. Chitra; V. Ramakrishnan (Institute of Advanced Engineering and Science, 2016)
The performance parameters such as viscosity, humidity and pressure of the gear box lubricating oil should be monitored and controlled to improve the efficiency of the windmill. The recent technique like IOT is used for the continuous transmission of bulk data of these parameters from one machine to other machine which is situated in remote locations .Also the development of mobile technology and web made the live monitoring easier. Thus transmission and sharing of data takes place without any time delay. The technology also helps to completely eliminate the assistance nearby the site. The large wind farms in coastal areas are easily and continuously monitored and the data are recorded from remote locations with the mobile technology having internet connections. This paper also reports the design of MEMS viscosity sensor,MEMS humidity sensor and MEMS pressure sensor for continuous monitoring of the lubricating system .The main advantage of implementing MEMS devices is to reduce the size and cost and also the sensitivity is improved. Along with IOT, smart sensor technology is also introduced in the monitoring which avoids the serious problems that occur in wind mills.The performance parameters such as viscosity, humidity and pressure of the gear box lubricating oil should be monitored and controlled to improve the efficiency of the windmill. The recent technique like IOT is used for the continuous transmission of bulk data of these parameters from one machine to other machine which is situated in remote locations .Also the development of mobile technology and web made the live monitoring easier. Thus transmission and sharing of data takes place without any time delay. The technology also helps to completely eliminate the assistance nearby the site.The large wind farms in coastal areas are easily and continuously monitored and the data are recorded from remote locations with the mobile technology having internet connections. This paper also reports the design of MEMS viscosity sensor,MEMS humidity sensor and MEMS pressure sensor for continuous monitoring of the lubricating system .The main advantage of implementing MEMS devices is to reduce the size and cost and also the sensitivity is improved. Along with IOT, smart sensor technology is also introduced in the monitoring which avoids the serious problems that occur in wind mills.